Meclizine Inhibits Pseudorabies Virus Replication by Interfering With Virus Entry and Release - Liu, Panrao; Hu, Danhe; Yuan, Lili; Lian, Zhengmin; Yao, Xiaohui; Zhu, Zhenbang; Nowotny, Norbert; Shi, Yi; Li, Xiangdong (Frontiers in Microbiology, 2021)
Pseudorabies virus (PRV) is a pathogen that causes substantial economic losses to the swine industry. With the emergence and widespread of PRV variants since 2011 in China, current commercial vaccines cannot provide complete protection against PRV infection. Therefore, antiviral drugs may work as an alternative way to control and prevent PRV. In this study, the inhibitory effects and underlying molecular mechanisms of meclizine against PRV were studied. Meclizine displayed a significant inhibitory effect against PRV when it was added either before, simultaneously with, or after virus infection. The inhibitory effect of meclizine occurred during viral entry and cell-to-cell spreading, but not at viral attachment into PK-15 cells. Meclizine also inhibited viral particle release at the late stage of infection. The antiviral effect of meclizine was tested in mice and the results showed that meclizine reduced the severity of clinical symptoms and the viral loads in tissues, and delayed the death, after PRV challenge. The above results indicated that meclizine had an inhibitory effect on PRV. Our findings will contribute to the development of potential therapeutic drugs against PRV infection.